Ageism and Job Advertisements: The Impact of Age Restrictions on Job Accessibility for Old Job Seekers in Indonesia - Siregar, Rahmat; Damanik AD, I Dewa Bagus Ryan; Manik, Vinta Ito (SOSHUM : Jurnal Sosial dan Humaniora, 2024)
This article explores the impact of ageism on job accessibility in Indonesia, focusing on the socio-economic and psychological effects of age restrictions in job advertisements on older job seekers. The research employs qualitative methods, using both secondary and primary data. Secondary data were gathered from job advertisements with age restrictions on platforms such as LinkedIn, Instagram (@kemnaker), and the WhatsApp group of the Old Jobseeker Indonesia community. Primary data were obtained through interviews with informants selected via purposive sampling, using Google Forms to collect potential informant data from online platforms like LinkedIn, the Old Jobseeker Indonesia WhatsApp group, and Instagram (@kemnaker) over a 10-day period from April 18 to April 27, 2024.The findings reveal that ageism is a selection practice that implicitly excludes job seekers by using age as a criterion, particularly for frontline roles. Moreover, ageism adversely affects the social, economic, and psychological well-being of job seekers in Indonesia, contributing to their exclusion from society at micro, meso, and macro levels. Age-based job advertisements also influence job seekers’ decisions to apply, as many perceive applying for these positions to be futile.